Racial disparities in the proportion of needed services maltreated children received. (November 2018) - Cheng, Tyrone C.; Lo, Celia C.
Abstract: This secondary analysis of data describing 1186 maltreated children, drawn from the National Survey of Child and Adolescent Well-Being II, examined racial disparities in their access to and receipt of needed services and in their caseworkers' case planning and engagement with caregivers. We used generalized least squares random-effects modeling for panel data, separately with 3 ethnicity subsamples, to estimate associations between proportion of needed services received and several explanatory variables. Children in these subsamples had been substantiated for maltreatment and had had at least one needed service identified by a caseworker. Results showed Hispanic children to receive proportionally fewer needed services versus White children. Moreover, across all subsamples, proportion of needed services received was associated negatively with client refusal of services and positively with interview wave. Results showed that proportionally more needed services were received by the subsample of 719 African American children living in poverty, relatively young, able to access services with little difficulty, and associated with case plans identifying relatively more needed services. For the subsample of 712 Hispanic children, negative associations were observed between services receipt and perceived collaborative engagement with caseworker reported by caregiver, as well as with service unavailability and with difficulty accessing services. Finally, results for the subsample of 720 White children who were physically maltreated and experienced service unavailability showed them to receive proportionally fewer needed services; however, White children whose case plans included needed services received proportionally more services. Implications for child welfare services and for caseworkers are discussed. Highlights: Needed services in case plan increased needed services received. Service unavailability, inaccessibility, and refusal reduced needed services received. Hispanic children received proportionally fewer needed services than White children. Worker-caregiver collaborative engagement reduced Hispanic children services receipt. Living with parent in poverty increased African American children services receipt.